Radiological evaluation of soft-tissue swellings - Rachna Chaurasia ,; Mohd. Abubakar,; Vishal Gupta, (Asian Journal of Medical Sciences, 2023)
Background: Soft-tissue swellings (STSs) are commonly encountered by a radiologist in routine practice, either as the principal indication for diagnostic examination or as an incidental finding during an examination performed for other indications. Aims and Objectives: The aim of the study was to design a basic approach for the evaluation of STS with the help of available imaging modalities (ultrasound [USG], computed tomography [CT], and magnetic resonance imaging [MRI]) and analyzes its imaging characteristics so as to arrive at its final diagnosis. Materials and Methods: This prospective study (CTRI/2023/01/048933) was conducted in the Department of Radio-diagnosis, MLBMC, Jhansi, Uttar Pradesh, with 100 cases of STS were primarily evaluated by high-resolution grayscale USG, out of 100 cases, 72 diagnosed on USG and rest equivocal cases were secondarily evaluated with MRI, out of which 25 diagnosed and three cases needed CT evaluation. Three cases were evaluated with MRI+CT scan and finally diagnosed. Diagnosed cases followed by histopathology and surgery. Results: In our study, we found that USG is helpful in benign and superficial STS, as 72/100 cases diagnosed with the help of USG. In equivocal, deeply located, and malignant cases, MRI is more helpful in making a final diagnosis. In our study out of 28 cases, 25 diagnosed on MRI. CT scan used as accessory modality in the diagnosis of STS. Conclusion: USG remains the first-line imaging modality for the assessment of STS. MRI is an excellent modality in equivocal or suspicious lesion for characterisation of nature and extension. CT can be used for the detection of calcification and bone involvement.